Studi Mengenai Penerapan dan Evaluasi Pola Koordinasi yang Digunakan dalam Penyelenggaraan Event Pancaverse. - Mochamad Amboro Alfianto; Akwilla Nathanael Odoh; Lazia Putri Widjiastuti; M. Alandra Bestama; Gilang Ramadan; Arif Ramdhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the ever-evolving creative industry, event management has evolved beyond mere entertainment to become a strategic tool for conveying messages and building public awareness. This study aims to examine the crucial role of coordination in the event production process, using the Pancaverse event, a case study that focused on a sustainable lifestyle. Using a descriptive qualitative approach, the study analyzes the coordination structure implemented, the cross-team communication system, and the challenges and solution strategies employed in the event's implementation. Data were collected through internal documentation, technical observations, and informal interviews with the organizing team. The results indicate that the success of the Pancaverse event was significantly influenced by a well-organized coordination structure, involving key roles such as the event director, stage manager, and vendor liaison. Each team had clear responsibilities, facilitating task allocation and ensuring the smooth running of the event. The use of communication tools such as walkie-talkies, instant messaging groups, and logistics applications significantly assisted in supporting real-time communication between teams, enabling them to stay connected and responsive to changes occurring on the ground. Obstacles encountered in the event implementation process, such as miscommunication, changes to the rundown, and external factors like weather and permits, were addressed through various strategies. Developing clear SOPs (Standard Operating Procedures), technical simulations to prepare for potential issues, and incorporating buffer time into the event rundown are effective solutions to address these issues. The findings of this study confirm that solid coordination is a key element in unifying the vision, streamlining operations, and delivering an event that is not only technically successful but also emotionally and educationally impactful for the audience. Coordination in an event is not merely a technical mechanism, but also a strategic foundation that is crucial for organizing an effective and meaningful event.